The complementarity of lean manufacturing practices with importance-performance analysis: how does it leverage inventory performance? - Nawanir, Gusman; Fernando, Yudi; Lim, Kong Teong (Inderscience Enterprises Ltd., 2021)
This paper aims to examine the effect of lean manufacturing (LM) implementation on inventory minimisation (IM) directly and indirectly [i.e., through manufacturing flexibility (MF) as a mediating variable]. This empirical study used a survey-based quantitative data through a cross-sectional research design and stratified random sampling technique for sample selection. A total of 236 large manufacturing companies were participated in the study. Four hypotheses were tested statistically by applying structural equation modelling (SEM) with Smart PLS 3.2.7. The finding revealed that in order to leverage MF and subsequently augment the inventory performance, LM should be applied in a holistic manner because of the complementary relationships among its practices. The importance-performance map analysis (IPMA) found the LM as the main driver of IM. Despite performing at the comparable level, LM has substantially higher importance than MF. Consequently, performance should be prioritised at the implementation of LM by focusing on the most important constructs of LM (i.e., TPM, quality control, quick setup and flexible resources). This study contributes to filling the existing gaps of limited studies investigating the effect of LM on both MF and IM. The practitioners will be benefited by understanding the vital constructs of LM to improve MF and inventory performance.